PENGEMBANGAN STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS MODERASI BERAGAMA PADA SEKOLAH MENENGAH ATAS - Muslim, M; Arifin, Muhammad; Samudi (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2024)
Tolerance, justice, balance, equality, diversity, example, laws and regulations, public interest, statehood and culture are the values ??of religious moderation which are important components in learning Islamic religious education. Therefore, a moderate attitude is one of the characters developed in Islamic religious education and has a strong portion in development. The aim of this research is to analyze the development of Islamic religious education learning strategies based on religious moderation in high schools in Banten. This research uses qualitative research of the phenomenological type with data collection using observation, interviews and documentation as well as data analysis using data reduction, data display and drawing conclusions. The research results found the development of Islamic religious education learning strategies, including: Planning: establishing various documents and policies related to religious moderation in schools. Implementation: insertion of religious moderation material, learning strategies, programs, education, training and provision regarding religious moderation. Evaluation: tests, surveys and questionnaires. It is hoped that this research will become a reference in developing learning strategies for Islamic religious education in schools.